2013
DOI: 10.2105/ajph.2013.301348
|View full text |Cite
|
Sign up to set email alerts
|

Nonprescribed Hormone Use and Self-Performed Surgeries: “Do-It-Yourself” Transitions in Transgender Communities in Ontario, Canada

Abstract: Past negative experiences with providers, along with limited financial resources and a lack of access to transition-related services, may contribute to nonprescribed hormone use and self-performed surgeries. Promoting training initiatives for health care providers and jurisdictional support for more accessible services may help to address trans people's specific needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
134
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(144 citation statements)
references
References 27 publications
6
134
1
3
Order By: Relevance
“…It is clear that the endocrine possibilities or limitations for this specific group are, so far, not described in the medical literature and indeed it is likely that a proportion of this group are self-medicating with the attendant risks (Rotondi et al, 2013). Further, cosmetic interventions may be sufficient to achieve partial feminization.…”
Section: A Discussion Of the Literaturementioning
confidence: 99%
“…It is clear that the endocrine possibilities or limitations for this specific group are, so far, not described in the medical literature and indeed it is likely that a proportion of this group are self-medicating with the attendant risks (Rotondi et al, 2013). Further, cosmetic interventions may be sufficient to achieve partial feminization.…”
Section: A Discussion Of the Literaturementioning
confidence: 99%
“…10 A study by Rotundi found that transgender people ready but not able to medically transition are more likely to have depressive symptoms than peers who have begun the process. 11 The ensuing combination of hopelessness and depression results in participation in high-risk sexual behaviors. 12 Nuttbrock et al recently found that gender-related abuse also caused depressive symptoms that predicted HIV and STIs for young transwomen.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Despite a 34-fold higher likelihood of having HIV among TW in the United States compared with the general population, 4 transgender people (approximately 0.4%-0.6% of the U.S. population 5,6 ) have comparatively low healthcare utilization rates 7 and may seek gender-affirming therapies (including HT and body modification services) outside of traditional, supervised medical settings. 8,9 Both HT and ART have potential side effects, and drug-drug interactions (DDI) may exist between some ART medications (such as nonnucleoside reverse transcriptase inhibitors [NNRTI] and protease inhibitors [PIs]) and HT (particularly ethinyl estradiol), 10 making unsupervised or uncoordinated HT and ART use potentially risky for TW taking feminizing HT. Limited data exist that address knowledge and consequences of ART and/or HT side effects and ART-HT DDIs among TW.…”
mentioning
confidence: 99%